Role of Intravitreal Antivascular Endothelial Growth Factor Injections for Choroidal Neovascularization due to Choroidal Osteoma - Mansour, Ahmad M. (Hindawi Publishing Corporation, 2014)
We treated 26 eyes of 25 young patients having a mean age of 30 years with intravitreal vascular endothelial growth factor (VEGF) inhibitor for choroidal new vessel (CNV) formation overlying choroidal osteoma over a mean follow-up of 26 months. Mean number of injections was 2.4 at 6 months, 3.2 at 12 months, and 5.5 at 24 months. CNV was subfoveal in 14 eyes, juxtafoveal in 5, extrafoveal in 5, and peripapillary in 2. By paired comparison, mean decrease from baseline was 119.7 microns at 6 months (n = 15; P = 0.001), 105.3 microns at 1 year (n = 10; P = 0.03), and 157.6 microns at 2 years (n = 7; P = 0.08). BCVA improved by 3.3 lines at 6 months after therapy (n = 26; P < 0.001), 2.8 lines (n = 20; P = 0.01) at 1 year, and 3.1 lines (n = 13; P = 0.049) at 2 years. We conclude that intravitreal anti-VEGF injections improve vision in majority of eyes with CNV from choroidal osteoma.